2012
DOI: 10.5120/8859-2818
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Neural Network Model and Mathematical Models for Prediction of Glucose Concentration during Enzymatic Hydrolysis

Abstract: Enzymatic hydrolysis of cellulose is a complex process because of a number of inhibition and enzyme inactivation reactions which happen during hydrolysis. Artificial Neural Networks (ANNs) are very effective in developing predictive models for processes involving complex reaction kinetics that would otherwise be difficult to be modeled by more traditional deterministic approaches. The present investigation was carried out to study the application of Artificial Neural Network as a tool for predicting glucose pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…This algorithm computes numerically the Jacobian matrix of the system, which permits to update weight and bias iteratively until minimising the error function (in our case MSE). Similarly, the Levenberg–Marquardt training algorithm was chosen by Nikzad et al to model the enzymatic hydrolysis of cellulose with an ANN comprising seven neurons in the hidden layer. This model was found to be more accurate than two phenomenological models chosen from literature.…”
Section: Resultsmentioning
confidence: 99%
“…This algorithm computes numerically the Jacobian matrix of the system, which permits to update weight and bias iteratively until minimising the error function (in our case MSE). Similarly, the Levenberg–Marquardt training algorithm was chosen by Nikzad et al to model the enzymatic hydrolysis of cellulose with an ANN comprising seven neurons in the hidden layer. This model was found to be more accurate than two phenomenological models chosen from literature.…”
Section: Resultsmentioning
confidence: 99%
“…However, enzymatic hydrolysis is considered the most promising strategy because it presents several advantages over chemical saccharification including high efficiency, low energy consumption due to the requirement of mild operation conditions, not environmental damage because enzymes are biodegradable, not toxic compounds formation and, low deterioration and corrosion problems for the equipment. Additionally, enzymatic hydrolysis produces fewer fermentation inhibitors [12,[32][33][34][35][36].…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
“…In another investigation, Choi et al [164] adapted the overall mass transfer coefficient in an air-lift bioreactor to the equation (31) for a temperature of 20°C as reference. Moreover, equations (32) and (33) represent mathematical expressions to determine k a L considering the diameter in bubble column reactors (D ) c . Shah et al [161] developed correlation shown in equation (34) to calculate the mass transfer coefficient using Froud and Galileo dimensionless numbers.…”
Section: Mass Transfer Coefficientmentioning
confidence: 99%
“…β-glucosidase catalyzes cleavage of cellobiose, which plays a significant role in the hydrolysis process, since cellobiose is an end product inhibitor of many cellulases including both exo-and endoglucanases Lee 1997;Rabinovich et al 2002;Sun and Cheng 2002). β-Glucosidase, in turn, is inhibited by glucose and, therefore, enzymatic hydrolysis is sensitive to the substrate concentration (Nikzad et al 2012). In addition to substrate concentration, pretreatment of cellulosic materials and hydrolyzing conditions such as temperature and pH are among factors influencing the efficiency of enzymatic hydrolysis.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%